Phase transitions in the Blume-Emery-Griffiths model on Cayley tree - Ganikhodjaev, Nasir; Idris, Amin (2012)
We consider the Blume-Emery-Griffiths model on the Cayley tree and investigate the problem of phase transition. It is found the exact value for the critical temperature and described the region of phase transition.